The effect of planting date in blooming season on three potato (Solanum tuberosum L.) cultivars in Sulaymaniyah location - Mohamad, Z.; Challab, Y. K.; Obaid, M. H. (Journal of Kerbala for Agricultural Sciences, 2014)
The study was set up during blooming season 2010 at agricultural research center (Canytanka) in directory of agricultural research in Sulaymaniyah. The effect of transplanting three potato cultivars Draga,Provento and Sante with two blooding season (10/3)and (25/3) on vegetative growth and the yield was the aim of this study. Factorial Randomized Completely Block Design (R.C.B.D.) with four replicates was used and data subjected to analysis of variance in addition to least significant differences (L.S.D.) with P=0.05 for comparison between treatment means.The results could be summarized as fallow Provento cultivar was significantly affected on plant high and number of tubers and gave (73.43 cm/plant and 12.00 tuber/plant) respectively while there were no significant differences in number of shoot ,stem diameter and number of leaves per plant parameters . Moreover the results revealed that the 25/3 bloming season was affected significantly on stem diameter , number of tubers as compare to plant height , number of shoot and total yield parameters .